EXTRALINGUISTIC FACTORS THAT GIVE RISE TO THE RELIGIOUS STYLE (Scientific journal of the Fergana State University, 2023)
The article discusses extralinguistic factors that give rise to the religious style. Linguistic (linguistic) factors structural and systemic features of a particular language - the system of phonemes, vocabulary, morpheme types, word-making models, grammatical construction, semantic and functional features of lexical, grammatical units, the rule that determines the connection and relationship between them-laws are numbered, extralinguistic (nonlinear) factors are factors that exist outside the language: forms of the social system, historicistations, economic, political, cultural and educational ties between peoples and nations, development of science, development of production, these are the laws and decrees on language and writing.